Pengaruh Model Pembelajaran Berbasis Game Terhadap Kemampuan Siswa dalam menentukan Majas pada Teks Puisi di Kelas VIII C SMPN 50 Kota Batam - Dinda Nur Dwi; Etik Triawahyuni; Fabio Testy Ariance Loren (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to improve the ability of class VIII C students of SMPN 50 Batam in determining figures of speech in poetry texts through the application of game-based learning models. The method used is a quasi-eksperimenta design with a pretest-posttest control group deisgn. The research sample consisted of two classes, namely the experimental class that received game-based learning and the control class that used conventional learning methods. The research instrument was a test of the ability to determine figures of speech in poetry texts. The data were analyzed using the normality and homogeneity prerequisite tests, then continued with hypothesis testing using the t-test. The results showed that the average value of the experimental class increased significantly compared to the control class. The significance value of the t-test was 0.009 < 0.05, which indicates that the game-based learning model has a positive and significant effect on students’ ability to determine figures of speech in poetry texts. Thus, the game-based learning model can be used as an alternative effective learning strategy in improving students’ understanding offigures of speech in poetry texts.